2017
DOI: 10.1103/physrevb.95.235406
|View full text |Cite
|
Sign up to set email alerts
|

Layer dependence of the electronic band alignment of few-layer MoS2 on SiO2 measured using photoemission electron microscopy

Abstract: Tailoring band alignment layer-by-layer using heterojunctions of two-dimensional (2D) semiconductors is an attractive prospect for producing next-generation electronic and optoelectronic devices that are ultra-thin, flexible, and efficient. 2D layers of transition metal dichalcogenides (TMDs) in laboratory devices have already shown favorable characteristics for electronic and optoelectronic applications. Despite these strides, a systematic understanding of how band alignment evolves from monolayer to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…By comparing optical microscopy images with PEEM images and performing spectroscopic PEEM measurements of the graphene samples studied here, we avoided areas with non-uniformities in optical or PEEM intensities. As a result, work function variations in graphene were resolved with PEEM on an energy scale (10s meV), similar to what was observed with as-grown MoS 2 37 . Graphene work function values (4.4 eV for 1 L graphene) measured here with PEEM are consistent with several prior works 15 , 16 , 35 .…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…By comparing optical microscopy images with PEEM images and performing spectroscopic PEEM measurements of the graphene samples studied here, we avoided areas with non-uniformities in optical or PEEM intensities. As a result, work function variations in graphene were resolved with PEEM on an energy scale (10s meV), similar to what was observed with as-grown MoS 2 37 . Graphene work function values (4.4 eV for 1 L graphene) measured here with PEEM are consistent with several prior works 15 , 16 , 35 .…”
Section: Methodssupporting
confidence: 68%
“…The relative energy scale was calibrated using the work function of 1LG, determined from photoemission yield measurements acquired by recording the photoemission intensity as a function of photon energy (for details of the data acquisition and processing, see ref. 37 ). The photoemission yield measurement itself did not yield sufficient statistics to bear a work function map of the same area due to the low photoemission intensity.…”
Section: Methodsmentioning
confidence: 99%
“…In recent times, it has been shown that the direct chalcogenization of Mo in vapor phase using MoO2 as a source leads to samples with optoelectronic grade quality which is important for applications that harness their optical and exciton-based properties. [110][111][112][113][114][115][116] While gas source-CVD and MBE have been used to deposit a variety of chalcogenide thin films, extension to the controlled synthesis of monolayer and fewlayer films and heterostructures presents new challenges. Specifically, reactors used in CVD techniques must be designed, and growth parameters chosen with the aim of achieving precise control over material uniformity and reproducibility.…”
Section: Milestonesmentioning
confidence: 99%
“…[17][18] The bandgap alignment for various MoS2 layers and PbS/CdS QDs emitting at 900nm are shown in Figure 1 maxima and conduction band (CB) minima were from literature. [9][10][11][12] Clearly, PbS/CdS QDs and layered MoS2 form a type-II heterojunction, which favors photoinduced electron transfer from QDs to MoS2, with the electron transfer expected to strengthen with the increase number of MoS2 layers due to an increase in electron transfer driving force. At the same time nonradiative transfer from photoexcited QDs to MoS2 can be ruled out as a possible quenching mechanism and this is because of the lack of spectral overlap between the absorption spectrum of MoS2 and the PL spectrum of core/shell PbS/CdS QDs.…”
mentioning
confidence: 99%